Synovial Chondromatosis of the Subacromial Bursa Causing a Bursal-Sided Rotator Cuff Tear - Julie A. Neumann; Grant E. Garrigues (Case Reports in Orthopedics)
Synovial chondromatosis is an uncommon condition, and involvement of the shoulder is even more rare. We report on a 39-year-old female who presented with symptoms, radiographic features, and intraoperative findings consistent with multiple subacromial loose bodies resulting in a partial-thickness, bursal-sided rotator cuff tear of the supraspinatus muscle. She was treated with an arthroscopic removal of loose bodies, complete excision of the subacromial/subdeltoid bursa, acromioplasty, and rotator cuff repair. To our knowledge, this is the first report of arthroscopic treatment for a bursal-sided, partial-thickness rotator cuff tear treated with greater than two-year clinical and radiographic follow-up. We utilized shoulder scores, preoperative and postoperative range of motion, and imaging to assess the results of treatment and surveillance for recurrence in our patient after two-year follow-up.